Improving candidate developability through deselection in mammalian display for therapeutic antibody discovery - Korhonen, Linnea (My University, 2026)
Monoclonal antibodies are increasingly used as immunotherapeutics due to their good affinity and specificity for their target. The discovery and development of immunotherapeutics is time-consuming and expensive, and over half of them fail during the process. Some of the late-stage failures could be avoided by considering the developability profile of an antibody candidate alongside its antigen affinity. Developability testing for large mammalian display libraries could be implemented by using a set of deselection reagents as a screening step. The aims in this thesis were to test the deselection step on mutated variant libraries to see if there were changes to reagent binding compared to the parental antibody, Sirukumab, and if the differentiation of closely related variants was possible. Two libraries were constructed by inducing mutations with error-prone PCR separately in the variable light and variable heavy regions (VL and VH, respectively) of Sirukumab. The libraries were transfected to Chinese hamster ovary (CHO) cells, using nocodazole treatment and recombinase mediated cassette exchange to enhance the transfection efficiency. The deselection reagent and antigen binding of both libraries and the parental antibody were measured using flow cytometry. The binding results revealed that almost all library variants lost expression. A small number of variants that retained the expression level had lost binding to reagents. No variant populations were seen that retained some of the expression but acquired reagent binding, which was an unexpected result. The deselection reagents seemed to be able to differentiate between the variants, since multiple different cell populations were seen in the result plots. In the future, a deselection step such as this one could be used in different stages of antibody discovery and development to ensure good developability.

Monoklonaalisia vasta-aineita käytetään yhä enemmän immunoterapeuttisina lääkkeinä, sillä ne omaavat hyvän affiniteetin ja spesifisyyden kohteeseensa. Uusien immunoterapeuttisten lääkkeiden kehitys on hidasta ja kallista, ja yli puolet niistä hylätään kehityksen aikana. Myöhäisen vaiheen epäonnistumista voitaisiin välttää ottamalla ajoissa huomioon vasta ainekandidaatin kehitettävyys affiniteetin ohella. Kehitettävyystestaus suurille nisäkässoluissa esiteltäville vasta-ainekirjastoille voitaisiin toteuttaa käyttämällä deselektioreagensseja varianttien seulomiseen. Tämän työn tavoitteena oli testata deselektioseulontaa vasta-ainekirjastoille, jotka oli luotu aiheuttamalla mutaatioita Sirukumab-nimiseen vasta-aineeseen. Tarkoituksena oli selvittää, sitoutuvatko reagenssit eri tavalla kirjastovariantteihin kuin Sirukumabiin, ja onko läheisten varianttien erottelu toisistaan mahdollista. Virhealttiilla PCR-reaktiolla tuotettiin erikseen mutaatioita Sirukumabin kevyen ja raskaan ketjun antigeenia sitovaan osaan, ja näistä muodostettiin kaksi kirjastoa. Kirjastot siirrettiin nisäkässoluihin hyödyntäen nokodatsolia sekä rekombinaasivälitteistä kasettivaihtoa transfektiotehokkuuden parantamiseksi. Deselektioreagenssien ja antigeenin sitoutumista kumpaankin kirjastoon sekä Sirukumabiin mitattiin virtaussytometrialla. Tulokset paljastivat lähes kaikkien kirjastovarianttien menettäneen ekspressiotason soluissa. Pieni osa varianteista säilytti ekspressiotason ja lakkasi sitoutumasta reagensseihin. Sellaisia varianttipopulaatioita, jotka olisivat säilyttäneet kohtalaisen ekspressiotason ja alkaneet sitoutua reagensseihin, ei nähty. Tämä tulos oli yllättävä. Deselektioreagenssit vaikuttivat pystyvän erottelemaan läheiset variantit toisistaan, sillä sirontakuvioissa erottui useita solupopulaatioita. Tulevaisuudessa tämänkaltaista deselektioseulontaa voitaisiin käyttää vasta-aineiden kehityksen eri vaiheissa hyvän kehitettävyyden varmistamiseksi.
Keywords: developability; mammalian display; error-prone PCR; recombinase mediated cassette exchange; nocodazole; deselection reagent; flow cytometry